Cardiac transplantation in transthyretin amyloid cardiomyopathy: outcomes from three decades of tertiary centre experience. (3rd October 2022) - Razvi, Y; Patel, R; Ioannou, A; Rauf, M U; Masi, A; Porcari, A; Blakeney, I; Kaza, N; Lachmann, H; Whelan, C; Venneri, L; Martinez-Naharro, A; et al.
Abstract: Background: Transthyretin cardiac amyloidosis (ATTR-CM) is a progressive and fatal cardiomyopathy. Treatment options in patients with advanced heart failure are limited to cardiac transplantation (CT). Despite small case series demonstrating comparable outcomes with CT between patients with ATTR-CM and non-amyloid cardiomyopathies, ATTR-CM is considered to be an absolute contraindication to CT in some centres. This is in part due to a perceived risk of amyloid recurrence in the cardiac allograft. We report outcomes of patients with ATTR-CM assessed at our centre whom underwent CT over the past thirty years. Methods: We retrospectively evaluated all ATTR-CM patients assessed at the UK National Amyloidosis Centre between 1990 and 2020 who underwent CT. Pre-transplantation disease and patient characteristics were determined and outcomes were compared with our large cohort of non-transplanted ATTR-CM patients. Censor date was 11th January 2022. Results: Eleven (9 male, 2 female) patients with ATTR-CM underwent CT including 8 with wild-type ATTR-CM and 3 with variant ATTR-CM (ATTRv). Median age at CT was 60.3 years and median follow up post-CT was 65.7 months. Median (range) NT-proBNP concentration pre-transplant was 4478ng/L (1057–8778ng/L), median (range) left ventricular ejection fraction (LVEF) was 39% (27–56%) and mean (IQR) interventricular septal (IVSD) was 18 mm (15.9–20.1 mm). 8 patients were NYHA functional class III, the 3 remaining patients were class II. One, three, and five-year survival was 100%, 89% and 86%, respectively and the longest surviving patient was censored >19 years post CT. Survival is at least comparable to UK and US CT outcome registry data for all non-amyloid patients undergoing CT. No patients had recurrence of amyloid in the cardiac allograft as assessed by endomyocardial biopsy and/or Tc-DPD scintigraphy. Two patients were commenced on Patisiran for amyloid polyneuropathy at 211 and 5 months post-CT. Graft rejection requiring treatment was observed in 2 patients, and successfully treated with intravenous steroids. Renal impairment was common, with 6 patients being left with chronic kidney disease. Three patients died, including one with ATTRv-CM from complications of leptomeningeal amyloidosis. Survival among the cohort of patients who underwent CT was significantly longer than UK patients with ATTR-CM generally (P≤0.006), regardless of NAC ATTR disease stage and including those diagnosed under 65 years of age (P=0.028). (Figure 1) All surviving patients were NYHA functional class I at time of censor. Conclusion: Our data indicates that cardiac transplantation is well tolerated, restores functional capacity, and prolongs survival in ATTR-CM with little risk of recurrence of amyloid in the cardiac allograft. We believe that our data argues strongly for ATTR-CM to be routinely included in the list of indications for cardiac transplantation. Funding Acknowledgement: Type of funding sources: None.